2014
DOI: 10.1016/j.neuron.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

More than Cholesterol Transporters: Lipoprotein Receptors in CNS Function and Neurodegeneration

Abstract: Members of the low-density lipoprotein (LDL) receptor gene family have a diverse set of biological functions that transcend lipid metabolism. Lipoprotein receptors have broad effects in both the developing and adult brain and participate in synapse development, cargo trafficking, and signal transduction. In addition, several family members play key roles in Alzheimer's disease pathogenesis and neurodegeneration. This review summarizes our current understanding of the role lipoprotein receptors play in CNS func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 243 publications
(290 reference statements)
3
120
0
1
Order By: Relevance
“…In that manner the current findings extend our understanding of the biology of apoER2 beyond its well-established role in CNS development and Alzheimer’s disease (30) and its recently revealed functions in endothelium (26;29). Immunohistochemical analysis of human placenta revealed that apoER2 is abundantly expressed in trophoblasts throughout gestation, and immunoblotting demonstrated that the receptor is also expressed in HTR-8/SVneo and SW.71 cells that retain the characteristics of trophoblasts in culture (33;34;36).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In that manner the current findings extend our understanding of the biology of apoER2 beyond its well-established role in CNS development and Alzheimer’s disease (30) and its recently revealed functions in endothelium (26;29). Immunohistochemical analysis of human placenta revealed that apoER2 is abundantly expressed in trophoblasts throughout gestation, and immunoblotting demonstrated that the receptor is also expressed in HTR-8/SVneo and SW.71 cells that retain the characteristics of trophoblasts in culture (33;34;36).…”
Section: Discussionsupporting
confidence: 61%
“…In another recent study we discovered that apoER2 in endothelium also mediate responses to apolipoprotein E3 that are beneficial to cardiovascular health (29), highlighting the complexities of apoER2 function even in a single cell type. The biology of apoER2 is best understood in neurons in which it is critically involved in central nervous system development and Alzheimer’s disease (30). In the current work, using cell culture and mouse models we tested the hypotheses that apoER2 is expressed in trophoblasts, and that apoER2 mediates trophoblast dysfunction and pregnancy complications induced by aPL.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evidence also links lipid metabolism to poor brain outcomes during aging. Thus, the strongest genetic risk factor for late-onset sporadic AD is having an ε4 allele of the gene encoding apolipoprotein E, a protein that transports cholesterol and lipoproteins (Lane-Donovan et al, 2014). Despite considerable investigation, however, the mechanism by which the ε4 APOE isoform endangers neurons is unclear and may not be the result of altered cholesterol metabolism.…”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Despite considerable investigation, however, the mechanism by which the ε4 APOE isoform endangers neurons is unclear and may not be the result of altered cholesterol metabolism. Two possibilities are that APOE ε4 lacks the antioxidant (HNE-scavenging) ability of APOE ε2 and ε3 (Pedersen et al, 2000), and that APOE ε4 alters trafficking of proteins (including APP) through the endosomal pathway (Lane-Donovan et al, 2014). …”
Section: Cellular and Molecular Hallmarks Of Brain Agingmentioning
confidence: 99%
“…Beyond its role in lipid metabolism, apoE is associated with atherosclerosis, neuronal repair and maintenance, inflammation and, possibly, immune response to infectious diseases 1 . Several studies have shown an association between the ε4 allele (rs429358) and age-related diseases such as coronary heart disease 2,3,4 , stroke 5 and Alzheimer's disease 6,7 . The effect of this genotype in mortality has also been widely investigated, but the results are not consistent across all populations 8,9,10,11 .…”
Section: Introductionmentioning
confidence: 99%